Conductive Paste

JP7635888B2Active Publication Date: 2025-02-26MURATA MFG CO LTD

Patent Information

Application Number
JP2024530345
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-26
Filing Date
2023-05-11
Publication Date
2025-02-26
Estimated Expiration
2043-05-11

Smart Images

  • Figure 0007635888000005
    Figure 0007635888000005
  • Figure 0007635888000001
    Figure 0007635888000001
  • Figure 0007635888000002
    Figure 0007635888000002
Patent Text Reader

Abstract

Provided is a conductive paste for an internal electrode of a layered ceramic capacitor, said conductive paste being capable of maintaining relatively high coverage even if the internal electrode constitutes a thin layer. The conductive paste is for forming an internal electrode (4, 5) of a layered ceramic capacitor (1) fabricated through a firing step and comprises a conductive metal powder, a ceramic powder, an organic solvent, and an organic binder. The conductive metal powder contains copper. At least a portion of the ceramic powder consists of an ABO3 type oxide having a specific ion radius in which the ratio of the ion radius in the 6-coordination of the element at the A site in ABO3 with respect to the ion radius in the 6-coordination of copper is 0.96-1.04.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive paste, and more particularly to a conductive paste for forming internal electrodes of a multilayer ceramic capacitor. [Background technology]

[0002] A multilayer ceramic capacitor generally comprises a laminate having a plurality of laminated dielectric layers made of ceramic and a plurality of internal electrodes respectively arranged along a plurality of interfaces between the dielectric layers, and a plurality of external electrodes provided on the outer surface of the laminate and electrically connected to the internal electrodes. The internal electrodes comprise a plurality of first internal electrodes and a plurality of second internal electrodes alternately arranged in the stacking direction of the laminate, and the external electrodes comprise a first external electrode electrically connected to the first internal electrodes and a second external electrode electrically connected to the second internal electrodes.

[0003] In order to miniaturize and increase the capacity of a multilayer ceramic capacitor with such a structure, it is necessary to thin the dielectric layers and internal electrodes and to increase the coverage (electrode continuity) of the internal electrodes. Generally, in the firing process for manufacturing a multilayer ceramic capacitor, the temperature at which the conductive metal particles contained in the conductive paste film that will become the internal electrodes sinter is lower than the temperature at which the ceramic that constitutes the dielectric layers sinters, so the metal particles contained in the internal electrodes sinter first. This causes a decrease in the coverage of the internal electrodes. In particular, in the case of an internal electrode that is thinned to a thickness of 1 μm or less, the coverage is easily decreased, and this decrease in coverage is likely to hinder an increase in capacity.

[0004] Therefore, in order to form a thin internal electrode with high coverage, it is necessary to increase the temperature at which the conductive metal particles contained in the conductive paste film that will become the internal electrode are sintered in the firing process during the manufacture of the multilayer ceramic capacitor. This allows the temperature at which the metal particles contained in the conductive paste film that will become the internal electrode are sintered to be closer to the temperature at which the ceramic that constitutes the dielectric layer begins to sinter, and the timing of contraction during sintering between the internal electrode and the dielectric layer can be brought closer. As a result, the coverage of the internal electrode is increased, and a large capacity can be achieved.

[0005] In order to increase the coverage of the internal electrodes and realize a large capacity by the above-mentioned method, it is known to add a ceramic material having a composition similar to that of the ceramic constituting the dielectric layer, that is, a co-material, to the conductive paste for forming the internal electrodes, as described in, for example, paragraph 0004 of Patent Document 1 (JP Patent Publication No. 2016-31807). By adding the co-material, the sintering timing of the metal particles contained in the conductive paste film to become the internal electrodes can be shifted to a higher temperature, and the temperature at which the metal particles contained in the conductive paste film are sintered can be brought closer to the temperature at which the ceramic constituting the dielectric layer is sintered. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-31807 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, even if a co-material is added to the conductive paste for forming the internal electrodes, it cannot be denied that the temperature at which the metal particles contained in the conductive paste sinter is still lower than the temperature at which the ceramic that constitutes the dielectric layer sinters, and further improvement is desired. In particular, for internal electrodes that are thinned, for example to a thickness of 1 μm or less, there is a strong demand for an effective solution to the problem of reduced coverage that inhibits increased capacity.

[0008] Therefore, the present invention has been made in consideration of such problems, and has an object to provide a conductive paste for forming internal electrodes that can maintain relatively high coverage even when the internal electrodes are made thin. [Means for solving the problem]

[0009] The present invention provides a conductive paste for forming internal electrodes of a multilayer ceramic capacitor, comprising a conductive metal powder, a ceramic powder, an organic solvent and an organic binder, and in order to solve the above-mentioned technical problems, the conductive metal powder comprises copper, and at least a portion of the ceramic powder is a powder made of an ABO3 type oxide having a specific ionic radius, in which the ratio of the ionic radius of the A site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination is 0.96 or more and 1.04 or less. Effect of the Invention

[0010] By forming the internal electrodes of a multilayer ceramic capacitor using the conductive paste according to the present invention, the coverage of the internal electrodes can be increased. Therefore, even if the internal electrodes are made thinner, the coverage of the internal electrodes can be maintained high, and the increase in capacitance of the multilayer ceramic capacitor can be prevented from being hindered. [Brief description of the drawings]

[0011] [Figure 1] 1 is a cross-sectional view that illustrates a multilayer ceramic capacitor 1 to which a conductive paste according to the present invention is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The structure of a multilayer ceramic capacitor 1 to which the conductive paste according to the present invention is applied will be described with reference to FIG.

[0013] The multilayer ceramic capacitor 1 includes a laminate 2. The laminate 2 includes a plurality of laminated dielectric layers 3 made of ceramic, and a plurality of internal electrodes 4 and 5 arranged along the interfaces between the plurality of dielectric layers 3. The internal electrodes 4 and 5 are classified into a plurality of first internal electrodes 4 and a plurality of second internal electrodes 5 arranged alternately in the lamination direction of the laminate 3. A first external electrode 6 and a second external electrode 7 are provided on the outer surface of the laminate 2, more specifically, on each of the opposing end faces. The first external electrode 6 is electrically connected to the first internal electrode 4, and the second external electrode 7 is electrically connected to the second internal electrode 5.

[0014] The dielectric layer 3 is made of a ceramic mainly composed of ABO3 (A is at least one of Ba, Ca and Sr, and B is at least one of Ti and Zr). The ceramic mainly composed of ABO3 may further contain at least one of Mn, Mg, Si, Y, Dy and Gd as a secondary component.

[0015] The internal electrodes 4 and 5 contain copper as a conductive component. Furthermore, as a characteristic composition, the internal electrodes 4 and 5 contain at least one selected from, for example, CuTiO3, CoTiO3, and CrTiO3. CuTiO3, CoTiO3, and CrTiO3 have an ilmenite crystal structure.

[0016] As will be seen from the experimental examples described later, in a preferred embodiment, the dielectric layer 3 is made of a ceramic containing at least one selected from BaTiO3, SrTiO3, and CaZrO3 as a main component, and the internal electrodes 4 and 5 contain copper as a conductive component and at least one selected from CuTiO3, CoTiO3, and CrTiO3 as a ceramic material, and further contain, as necessary, at least one selected from BaTiO3, SrTiO3, and CaZrO3 contained in the dielectric layer 3.

[0017] The external electrodes 6 and 7 are formed, for example, by applying a conductive paste containing Ag or Cu as a main conductive component to the end faces of the laminate 2 and baking the paste. If necessary, for example, Ni plating and Sn plating may be applied on the thick film formed by baking.

[0018] The multilayer ceramic capacitor 1 is manufactured, for example, through the following steps. First, a ceramic slurry containing ceramic raw material powder having the above-mentioned composition is prepared. Next, a suitable sheet forming method is applied to the ceramic slurry to form ceramic green sheets. Next, a conductive paste to be each of the internal electrodes 4 and 5 is applied by printing or the like onto a predetermined ceramic green sheet among the plurality of ceramic green sheets. Next, the plurality of ceramic green sheets are stacked and then pressed together to obtain a green laminate. Next, the green laminate is fired. In this firing step, the ceramic green sheets become the dielectric layers 3. After that, the external electrodes 6 and 7 are formed on the end faces of the laminate 3.

[0019] The conductive paste to become the internal electrodes 4 and 5 used in manufacturing the multilayer ceramic capacitor 1 described above is preferably prepared as follows.

[0020] The conductive paste is produced by carrying out a first step of preparing a ceramic powder slurry containing a ceramic powder, an organic solvent and a dispersant, a second step of preparing a metal powder slurry containing a conductive metal powder, an organic solvent and a dispersant, a third step of preparing an organic vehicle containing an organic resin component and an organic solvent, and a fourth step of mixing the ceramic powder slurry, the metal powder slurry and the organic vehicle.

[0021] More specifically, in the first step, a ceramic powder slurry is prepared by mixing a ceramic powder and a dispersant in an organic solvent.

[0022] The ceramic powder may be, for example, at least one selected from CuTiO3, CoTiO3, and CrTiO3 as an ABO3 oxide, and may further contain at least one selected from BaTiO3, SrTiO3, and CaZrO3 as a co-material.

[0023] Since the conductive metal powder contained in the metal powder slurry produced in the second step described below contains copper, the above-mentioned ABO3 oxides, CuTiO3, CoTiO3 and CrTiO3, are ABO3 type oxides with specific ionic radii, in which the ratio of the ionic radius of the A-site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination is 0.96 or more and 1.04 or less.

[0024] The ceramic powder consisting of at least one selected from CuTiO3, CoTiO3 and CrTiO3 as the ABO3 oxide can suppress the reaction that may occur with the copper powder contained in the metal powder slurry produced in the second step during firing. The ceramic powder contains the ABO3 oxide as the main component, and may further contain at least one of Mn, Mg, Si, Y, Dy and Gd as a subcomponent. When such a subcomponent is contained, the grain growth of the ceramic particles is further suppressed, and the sintering of the metal particles may be more effectively suppressed.

[0025] As the dispersant mixed with the ceramic powder in the first step, for example, an anionic polymer dispersant can be used, and as the organic solvent, for example, dihydroterpineol can be used.

[0026] In the second step, a metal powder slurry is prepared by mixing a conductive metal powder and a dispersant with an organic solvent. The conductive metal powder is a powder made of copper or an alloy thereof. The dispersant and organic solvent used in the second step may be the same as those used in the first step.

[0027] In the third step, an organic vehicle is prepared by mixing an organic resin component with an organic solvent. For example, an ethyl cellulose resin can be used as the organic resin component. The organic solvent used in the third step can be the same as that used in the first step.

[0028] In the fourth step, the ceramic powder slurry, the metal powder slurry, and the organic vehicle are mixed together to obtain a conductive paste that will become the internal electrodes 4 and 5. This conductive paste contains a ceramic powder slurry, and as described above, the ceramic powder slurry contains at least one ceramic powder selected from CuTiO3, CoTiO3, and CrTiO3 as ABO3 oxides with a specific ionic radius. Therefore, the internal electrodes 4 and 5 of the multilayer ceramic capacitor 1 manufactured through the firing step contain at least one selected from CuTiO3, CoTiO3, and CrTiO3.

[0029] [Experimental Example] Next, an example of an experiment carried out to confirm the effects of the present invention will be described.

[0030] In this experimental example, copper powder was prepared as the conductive metal powder contained in the conductive paste for forming internal electrodes.

[0031] On the other hand, in addition to CuTiO3, CoTiO3, and CrTiO3, BaTiO3, CaZrO3, and SrTiO3 were prepared as ABO3 oxides with specific ionic radii that constitute the ceramic powder contained in the conductive paste for forming the internal electrodes. Table 1 shows the "crystal structure," "coordination number," "A-site element," and "ionic radius" for these ABO3 oxides. Note that Ba, Ca, and Sr have 12 coordination numbers in the original perovskite structure, but when Ba, Ca, and Sr are dissolved in the sites of the 6-coordinate elements (Cu, Co, Cr) in the ilmenite structure, they also become 6-coordinate, so the "ionic radius" in Table 1 shows the value for 6 coordination numbers.

[0032] [Table 1]

[0033] Below, experimental examples 1, 2, and 3 will be described, which were carried out by changing the ceramic raw material constituting the dielectric layer.

[0034] (Experimental Example 1) Main component of the ceramic that makes up the dielectric layer: BaTiO3 1. Preparation of BaTiO3-based ceramic raw material for the dielectric layer As starting materials, powders of BaCO3 and TiO2 as main components were weighed, mixed in a ball mill for 72 hours, and then heat-treated at a top temperature of 1000°C for 2 hours to obtain heat-treated powder. On the other hand, powders of MnO, Dy2O3, MgO, SiO2, and BaCO3 were prepared as subcomponents, and the subcomponent powders were weighed so that the composition ratio of the above heat-treated powder was 100BaTiO3+0.5Mn+1.0Dy+1.0Mg+1.0Si+2.0Ba. These subcomponent powders were added to the above heat-treated powder, mixed in a ball mill for 24 hours, and then dried to obtain BaTiO3-based ceramic raw material powder.

[0035] 2. Preparation of conductive paste for forming internal electrodes The "ABO3 oxide" powder shown in Table 2 below and the BaTiO3-based ceramic raw material powder for the dielectric layers were used as the ceramic powder contained in the conductive paste for forming the internal electrodes.

[0036] These "ABO3 oxide" powders and BaTiO3-based ceramic raw material powders were weighed out to obtain the "addition ratio" shown in Table 2. These powders were premixed with dihydroterpineol as an organic solvent and an anionic polymer dispersant as a dispersant in a media-free agitation mill, and then dispersed in a media agitation mill to produce a ceramic powder slurry (Step 1).

[0037] On the other hand, copper powder as a conductive metal powder, dihydroterpineol as an organic solvent, and an anionic polymer dispersant as a dispersant were dispersed in a three-roll mill to prepare a metal powder slurry (second process).

[0038] Furthermore, an ethyl cellulose resin as an organic resin component and dihydroterpineol as an organic solvent were mixed together to obtain an organic vehicle (third step).

[0039] Thereafter, the metal powder slurry and the ceramic powder slurry were added to the organic vehicle and mixed and dispersed to prepare a conductive paste for forming internal electrodes (fourth step).

[0040] Table 2 shows the ratio of the ionic radius of the A-site element in 6-coordination to the ionic radius of copper in 6-coordination to be included in the internal electrode, i.e., the "ionic radius ratio (A-site element / metallic copper)." For sample 7, the ratio of the ionic radius of Ba element in 6-coordination (1.35 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.

[0041] 3. Fabrication of Multilayer Ceramic Capacitors A ceramic slurry containing the BaTiO3-based ceramic raw material powder prepared in 1 above was prepared, and then the ceramic slurry was subjected to a doctor blade method to form ceramic green sheets. Next, the conductive paste for forming internal electrodes prepared in 2 above was applied by screen printing onto a predetermined ceramic green sheet among the plurality of ceramic green sheets. Next, the plurality of ceramic green sheets were stacked and then pressed together to obtain a green laminate. Next, the green laminate was fired. After that, external electrodes were formed on the end faces of the sintered laminate to produce a sample multilayer ceramic capacitor.

[0042] 4. Evaluation

[0043] [Table 2]

[0044] An internal electrode and a dielectric layer located at the center in the height direction of a laminate included in a sample multilayer ceramic capacitor were peeled off from each other by electrochemical peeling.

[0045] Next, the center of the exposed internal electrode (1 / 2 in the width direction and 1 / 2 in the length direction) was observed using a microscope at 100x magnification. The obtained image was then analyzed to determine the percentage of the area of ​​the exposed portion that was occupied by the conductive film as the internal electrode, as the "coverage" shown in Table 2. "Coverage" of 80% or more was judged as good, with a "○" entered in the "Evaluation" column, and "Coverage" of less than 80% was judged as poor, with an "X" entered in the "Evaluation" column.

[0046] 5. Discussion The evaluation of samples 1 to 6 in Table 2 is "○". In these samples 1 to 6, the internal electrodes contain any of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxide. The internal electrodes also contain copper as a conductive component.

[0047] Here, looking at the ionic radius, first, the ionic radius of copper in 6-coordination is 0.77 Å, as shown in the "CuTiO3" section of Table 1. On the other hand, the ionic radius of the A-site element in each of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxides contained in the internal electrodes of samples 1 to 6 in 6-coordination is 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.

[0048] In samples 1 to 6 evaluated as “○”, the ratio of the ionic radius of the A site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination, i.e., the “ionic radius ratio”, is 0.96 or more and 1.04 or less.

[0049] In this way, the ionic radius of the A-site element in ABO3 in CuTiO3, CoTiO3, and CrTiO3 in samples 1 to 6 is equal to or close to the ionic radius of copper in six-coordination as the conductive metal to be included in the internal electrode, so the energy difference with the copper in the internal electrode is zero or small, and the oxide remains without being expelled from the internal electrode portion, which acts to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage of samples 1 to 6 was high at 84% or more.

[0050] Also, as in samples 4 to 6, the additive ratios of CuTiO3, CoTiO3 and CrTiO3 are not necessarily 100%, and as long as they are 10% or more, the effect of improving coverage was observed compared to cases in which none of CuTiO3, CoTiO3 and CrTiO3 was included. It is also noteworthy that in Experimental Example 1, the coverage of samples 4 to 6, in which the additive ratios of CuTiO3, CoTiO3 and CrTiO3 are 10%, shows the same value as the coverage of samples 1 to 3, in which the additive ratios are 100%.

[0051] In contrast, in sample 7, which was evaluated as "x", only BaTiO3 as a co-material was added to the internal electrode. In this case, Ba, which is an element in the A site of the ABO3 of the perovskite structure, has 12 coordination numbers, but when it dissolves in the A site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A site of the ilmenite structure, and the ionic radius of Ba at 6 coordination numbers is 1.35 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ba at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.75. Therefore, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and the coverage was low at 74%.

[0052] In sample 7, the "ionic radius ratio" was outside the range of 0.96 or more and 1.04 or less, and BaTiO3 was expelled from the internal electrode portion, which is presumably why the heat resistance of the internal electrode did not improve and the coverage was reduced.

[0053] (Experimental Example 2) Main component of the ceramic that makes up the dielectric layer: CaZrO3 1. Preparation of CaZrO3-based ceramic raw material for the dielectric layer As starting materials, the main components CaCO3 and ZrO2 powders, and the sub-components MnO, SiO2 and MgO powders were weighed out and mixed in a ball mill for 72 hours, after which the mixture was heat-treated at a top temperature of 1000°C for 2 hours to obtain a CaZrO3-based ceramic raw material powder.

[0054] 2. Preparation of conductive paste for forming internal electrodes The "ABO3 oxide" powder shown in Table 3 below and the CaZrO3 ceramic raw material powder for the dielectric layers were used as the ceramic powder contained in the conductive paste for forming the internal electrodes.

[0055] These "ABO3 oxide" powders and CaZrO3-based ceramic raw material powders were weighed out to obtain the "addition ratio" shown in Table 3, and a conductive paste for forming internal electrodes was prepared through the same process as in Experimental Example 1 above.

[0056] Table 3 shows the "ionic radius ratio (A-site element / metallic copper)" as in Table 2. For sample 17, the ratio of the ionic radius of Ca element in 6-coordination (1.00 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.

[0057] 3. Fabrication of Multilayer Ceramic Capacitors A ceramic slurry containing the CaZrO3-based ceramic raw material powder prepared in 1 above was prepared, and then the ceramic slurry was formed into ceramic green sheets by applying a doctor blade method. After that, a multilayer ceramic capacitor sample was prepared through the same steps as in Experimental Example 1.

[0058] 4. Evaluation

[0059] [Table 3]

[0060] Following the same procedure as in Experimental Example 1, the "coverage" was determined as shown in Table 3 and evaluated in the same manner.

[0061] 5. Discussion The evaluation of samples 11 to 16 in Table 3 is "○". In these samples 11 to 16, the internal electrodes contain any of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxide. The internal electrodes also contain copper as a conductive component.

[0062] Here, looking at the ionic radius, first, the ionic radius of copper in 6-coordination is 0.77 Å, as shown in the "CuTiO3" section of Table 1. On the other hand, the ionic radius of the A-site element in each of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxides contained in the internal electrodes of Samples 11 to 16 in 6-coordination is 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.

[0063] In samples 11 to 16 evaluated as “○”, the ratio of the ionic radius of the A site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination, i.e., the “ionic radius ratio”, is 0.96 or more and 1.04 or less.

[0064] In this way, the ionic radius of the A-site element in ABO3, CuTiO3, CoTiO3, and CrTiO3, in samples 11 to 16, in 6-coordination is equal to or close to the ionic radius of copper in 6-coordination as the conductive metal to be contained in the internal electrode, and therefore the energy difference with the copper in the internal electrode is zero or small, and so the oxide remains without being expelled from the internal electrode portion, thereby acting to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage in samples 11 to 16 was high, at 81% or more.

[0065] Also, like samples 14 to 16, the addition ratio of CuTiO3, CoTiO3 and CrTiO3 is not necessarily 100%, and as long as it is 10% or more, an effect of improving coverage was observed compared to cases where none of CuTiO3, CoTiO3 and CrTiO3 was included.

[0066] In contrast, in sample 17, which was evaluated as "x", only CaZrO3 was added as a co-material to the internal electrode. In this case, Ca, which is the A-site element in ABO3 of the perovskite structure, has 12 coordination numbers, but when it dissolves in the A-site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A-site of the ilmenite structure, and the ionic radius of Ca at 6 coordination numbers is 1.00 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ca at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.30. Therefore, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and the coverage was low at 72%.

[0067] In sample 17, the "ionic radius ratio" was outside the range of 0.96 or more and 1.04 or less, and it is presumed that CaZrO3 was expelled from the internal electrode portion, the heat resistance of the internal electrode was not improved, and the coverage was reduced.

[0068] (Experimental Example 3) Main component of the ceramic that makes up the dielectric layer: SrTiO3 1. Preparation of SrTiO3-based ceramic raw material for the dielectric layer As starting materials, the main component powders of SrCO3 and TiO2, and the sub-components powders of MnO, SiO2 and MgO were weighed out and mixed in a ball mill for 72 hours, after which the mixture was heat-treated at a top temperature of 1000°C for 2 hours to obtain SrTiO3-based ceramic raw material powder.

[0069] 2. Preparation of conductive paste for forming internal electrodes The "ABO3 oxide" powder shown in Table 4 below and the SrTiO3 ceramic raw material powder for the dielectric layers were used as the ceramic powder contained in the conductive paste for forming the internal electrodes.

[0070] These "ABO3 oxide" powders and SrTiO3-based ceramic raw material powders were weighed out to obtain the "addition ratio" shown in Table 4, and a conductive paste for forming internal electrodes was prepared through the same process as in Experimental Example 1 above.

[0071] Table 4 shows the "ionic radius ratio (A-site element / metallic copper)" as in Table 2. For sample 27, the ratio of the ionic radius of Sr element in 6-coordination (1.18 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.

[0072] 3. Fabrication of Multilayer Ceramic Capacitors A ceramic slurry containing the SrTiO3-based ceramic raw material powder prepared in 1 above was prepared, and then the ceramic slurry was formed into ceramic green sheets by applying a doctor blade method. After that, a multilayer ceramic capacitor sample was produced through the same steps as in Experimental Example 1.

[0073] 4. Evaluation

[0074] [Table 4]

[0075] Following the same procedure as in Experimental Example 1, the "coverage" was determined as shown in Table 4 and evaluated in the same manner.

[0076] 5. Discussion The evaluation of samples 21 to 26 in Table 4 is "○". In these samples 21 to 26, the internal electrodes contain any one of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxide. The internal electrodes also contain copper as a conductive component.

[0077] Here, looking at the ionic radius, first, the ionic radius of copper in 6-coordination is 0.77 Å, as shown in the "CuTiO3" section of Table 1. On the other hand, the ionic radius of the A-site element in each of CuTiO3, CoTiO3, and CrTiO3 as the ABO3 oxides contained in the internal electrodes of Samples 21 to 26 in 6-coordination is 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.

[0078] In samples 21 to 26 evaluated as “◯”, the ratio of the ionic radius of the A site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination, i.e., the “ionic radius ratio”, is 0.96 or more and 1.04 or less.

[0079] In this way, the ionic radius of the A-site element in ABO3, CuTiO3, CoTiO3, and CrTiO3, in samples 21 to 26, in 6-coordination is equal to or close to the ionic radius of copper in 6-coordination as the conductive metal to be contained in the internal electrode, and therefore the energy difference with the copper in the internal electrode is zero or small, and so the oxide remains without being expelled from the internal electrode portion, thereby acting to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage in samples 21 to 26 was high, at 80% or more.

[0080] Also, like samples 24 to 26, the addition ratio of CuTiO3, CoTiO3 and CrTiO3 is not necessarily 100%, and as long as it is 10% or more, an effect of improving coverage was observed compared to cases where none of CuTiO3, CoTiO3 and CrTiO3 was included.

[0081] In contrast, in sample 27, which was evaluated as "x", only SrTiO3 as a co-material was added to the internal electrode. In this case, Sr, which is an element in the A site of the perovskite structure ABO3, has 12 coordination numbers, but when it dissolves in the A site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A site of the ilmenite structure, and the ionic radius of Sr at 6 coordination numbers is 1.18 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Sr at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.53. Therefore, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and the coverage was low at 70%.

[0082] In sample 27, the “ionic radius ratio” was outside the range of 0.96 or more and 1.04 or less, and it is presumed that SrTiO3 was expelled from the internal electrode portion, the heat resistance of the internal electrode was not improved, and the coverage was reduced.

[0083] In the above-described Experimental Examples 1 to 3, the powder consisting of an ABO3 type oxide with a specific ionic radius as at least a part of the ceramic powder contained in the conductive paste was at least one selected from CuTiO3, CoTiO3, and CrTiO3, but it may be other than these. That is, the ABO3 type oxide with a specific ionic radius may be any ABO3 type oxide as long as the ratio of the ionic radius of the A-site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination contained in the conductive paste is 0.96 or more and 1.04 or less.

[0084] The embodiments of the present invention include the following.

[0085] <1> A conductive paste for forming an internal electrode of a multilayer ceramic capacitor, comprising a conductive metal powder, a ceramic powder, an organic solvent, and an organic binder, The conductive metal powder comprises copper; A conductive paste, wherein at least a portion of the ceramic powder is a powder made of an ABO3 type oxide having a specific ionic radius, in which the ratio of the ionic radius of the A site element in ABO3 in 6-coordination to the ionic radius of copper in 6-coordination is 0.96 or more and 1.04 or less.

[0086] <2> The ABO3 type oxide having a specific ionic radius has an ilmenite crystal structure. <1> The conductive paste according to claim 1.

[0087] <3> The ABO3 type oxide having a specific ionic radius is at least one selected from CuTiO3, CoTiO3, and CrTiO3. <2> The conductive paste according to claim 1.

[0088] <4> 10% by volume or more of the ceramic powder is a powder consisting of an ABO3 type oxide having the specific ionic radius, and the remainder of the ceramic powder is a powder mainly composed of at least one selected from BaTiO3, SrTiO3, and CaZrO3. <1> Or <3> 13. The conductive paste according to claim 12, [Explanation of symbols]

[0089] 1. Multilayer ceramic capacitors 2. Laminate 3 Dielectric Layer 4,5 Internal electrode 6,7 External electrode

Claims

1. A conductive paste for forming an internal electrode of a multilayer ceramic capacitor, comprising a conductive metal powder, a ceramic powder, an organic solvent, and an organic binder, The conductive metal powder comprises copper; At least a portion of the ceramic powder has an ABO 3 ABO having a specific ionic radius in which the ratio of the ionic radius of the A site element in 6-coordination is 0.96 or more and 1.04 or less. 3 Conductive paste, which is a powder consisting of oxides of the type.

2. ABO of the specific ionic radius 3 2. The conductive paste of claim 1, wherein the type oxide has an ilmenite crystal structure.

3. ABO of the specific ionic radius 3 The oxide of the type is CuTiO 3 , CoTiO 3 and CrTiO 3 The conductive paste according to claim 2 , which is at least one selected from the following:

4. 10% by volume or more of the ceramic powder is ABO having the specific ionic radius 3 The remainder of the ceramic powder is BaTiO 3 , SrTiO 3 and CaZrO 3 4. The conductive paste according to claim 1, which is a powder containing at least one selected from the following as a main component.

Citation Information

Patent Citations

  • JP1974056822A

  • Conductive paste and laminated electronic component, and their manufacturing method

    JP2001284162A

  • Conductive paste composition for internal electrode and multilayer ceramic electronic component including the same

    JP2013214698A

  • Method for producing composite powder and conductive thick film paste and multilayer ceramic electronic component using composite powder obtained by the production method

    JP2015083714A

  • Conductive paste and production method of the same

    JP2016031807A

Cited By

  • Multilayer ceramic capacitor

    JPWO2024181021A1